Learn Habituation - Sri Gustina Rambe; Neviyarni Neviyarni (Jurnal Neo Konseling, 2021)
Habits are created because of something accustomed, so that habits can be referred to as actions or skills always, not changing for a long time, so that those deeds and skills can really be recognized and the conclusion becomes a routine that is hard to leave. Routine can also be referred to as the motion of an action that runs easily and seems to run by itself. This action was initially caused by the mind that carried out the consideration and planning, so that later it would lead to actions which if this act were repeated so that it would become a routine.